Spatial concentrations of Lead and Copper in bottom sediments of Langkawi coastal area, Malaysia - Yunus, Kamaruzzaman; Muhamad Tajudin, Nur Shuhada; John, Akbar; Saad, Shahbudin; Khan Chowdhury, Ahmed Jalal; Ong, Meng Chuan; Al-Barwani, Said Mohd; Goddard, J Stephen (Academic Journals Inc., USA, 2011)
Surface sediment samples were collected from 5 different zones of the Langkawi coastal waters, Malaysia to determine the concentration of Lead (Pb) and Copper (Cu) by using the sensitive Inductively Coupled Plasma Mass Spectrometer (ICP-MS). The concentration of heavy metals was compared with the world average concentration of shale values. It was found that the total concentration of Pb was between 12.25 and 71.38 μg g-1 dw with mean concentration value of 41.87±7.30 μg g-1 dw which was two fold higher than the average shale value (20 μg g-1). Statistical analysis showed that the significant variation in Pb concentration between different sampling stations (p<0.05). Copper (Cu) concentration was ranged between 0.40 and 30.95 μg g-1 dw with mean concentration of 11.19±5.2 μg g-1 dw which was lower than the average shale value (45 μg g-1 dw). Enrichment Factor (EF) showed that source of Pb concentration in the study area was partially due to anthropogenic activities and the source of Cu was dominantly from terrigenous in origin. Results of the analysis showed that a coastal area of Langkawi is facing moderate metal pollution with increased rate of deposition.